Digital Marketing, Motivation, and University Image: Key Drivers Of University Choices - Hendrya Kurniawan; Astri Ayu Purwati; Yanti Mayasari Ginting; Siti Intan Nurdiana Wong Abdullah (Yayasan Pendidikan Islam Al-Matani, 2024)
This study aims to analyze the effect of digital marketing, motivation and university image on college interest and college decisions in the Master of Management Study program at Pelita Indonesia Institute of Business and Technology. This research is quantitative research The population in the study were students of the IBT PI Master of Management study program in the 2022/2023 academic year. The population of this study was 296 people, the sampling method used was probability sampling. The sampling technique used is simple random sampling The sample size used in this study was 75 respondents, using the Slovin formula. The results of this study indicate that digital marketing has a significant effect on college interest, motivation has a significant effect on college interest, university image has a significant effect on college interest, Digital marketing has an insignificant effect on college decisions, motivation has a significant effect on college decisions, university image has an insignificant effect on college decisions and college interest has a significant effect on college decisions